Understanding the value of cancer drugs–the devil is in the detail. Issue 15 (10th May 2016) - Goldstein, Daniel A.
Abstract : New tools to assess the value of cancer drugs are not sufficiently detailed. Economic modeling provides the ideal method with which to assess their value.